2002
DOI: 10.1038/sj.gt.3301787
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging and radioiodine therapy following sodium iodide symporter gene transfer in animal model of intracerebral gliomas

Abstract: Radioactive iodide uptake (RAIU)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 25 publications
1
65
0
1
Order By: Relevance
“…In our previous study, we showed that ex vivo NIS gene transfer to F98 rat glioma cells conferred a moderate survival benefit in 131 I-treated rats bearing intracerebral F98/hNIS gliomas. 5 In the present study, we show that the 131 …”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…In our previous study, we showed that ex vivo NIS gene transfer to F98 rat glioma cells conferred a moderate survival benefit in 131 I-treated rats bearing intracerebral F98/hNIS gliomas. 5 In the present study, we show that the 131 …”
Section: Introductionsupporting
confidence: 54%
“…5 The finding that 131 I therapeutic effectiveness in F98/hNIS gliomas was dose-dependent suggests that dose escalation could further improve the efficacy of NIS-targeted 131 I therapy. The validation of NIS-targeted 131 I therapy in another animal model further supports our hypothesis that NIS-mediated radionuclide therapy may be useful to circumvent the problem of a narrow therapeutic window intrinsic to brain tumor radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Recent developments in gene therapy have led to a number of studies aimed at introducing NIS expression in other tumor types, to provide for radioiodide imaging and therapy. [9][10][11][12][13][14][15][16] The ability to introduce NIS expression into ovarian tumors would be highly beneficial. Along with an extended proven record in radioiodide therapy of thyroid disease, NIS offers a major advantage as a therapeutic gene because it provides for imaging to confirm targeted expression of the protein before proceeding to therapy.…”
Section: Introductionmentioning
confidence: 99%
“…30 The human sodium-iodide symporter (hNIS) is a transmembrane ion symporter that concentrates iodide in thyroid follicular cells and is being evaluated as a therapeutic gene for the treatment for cancer. 31,32 To facilitate the noninvasive monitoring of oncolytic MV and to enhance its oncolytic efficiency, the virus was engineered to express hNIS (MV-NIS). Radioiodine was concentrated in MV-NIS-infected cells and the concentration of radioiodine increased as the MV-NIS infection progressed.…”
Section: Measles Virusmentioning
confidence: 99%